Comparative Analysis between Spinning and Other Causes in Exercise-Induced Rhabdomyolysis - Do Won Shim; Sung Youl Hyun; Jae Hyug Woo; Jae Ho Jang; Jae Yeon Choi (Journal of Trauma and Injury)
Purpose Spinning-induced rhabdomyolysis (SIR) has been increasing in recent years and accounts for a large proportion of exercise-induced rhabdomyolysis (EIR). The purpose of this study was to compare the clinical features between SIR and non-spinning exercise-induced rhabdomyolysis (NSIR), and to analyze each of these clinical features. Methods A retrospective chart review was conducted on patients treated due to EIR from January 2006 to March 2018. Patients were divided into the SIR and NSIR groups, and their clinical factors, outcome, and blood chemistries were compared and analyzed. Results Sixty-two patients were enrolled in this study, with 23 (37.1%) and 39 (62.9%) patients categorized in the SIR and NSIR groups, respectively. The SIR group were mostly women (78.3% vs. 38.5%, p=0.002), more f requent EIR occurrence in the first exercise class (60.9% vs. 15.4%, p=0.001), and had most complaints of thigh pain (91.3% vs. 43.6%, p=0.001). The SIR group had a higher incidence rate despite its shorter exercise duration (90.5% vs. 62.9%, p=0.024), longer hospital stay (6.0 [4.5–7.0] vs. 5.0 [3.5–6.0] days, p=0.080), and higher rate of peak CPK (15,000 U/L or higher) (91.3% vs. 74.4%, p=0.182) compared to the NSIR group. Conclusions SIR occurs at a higher rate during the first exercise class in women compared to NSIR, and the incidence rate is higher in SIR than in NSIR despite its shorter exercise duration (less than 60 minutes). It is necessary to recognize these risks during spinning exercises and to perform these exercises sequentially and systematically.